2023
DOI: 10.3390/biology12030444
|View full text |Cite
|
Sign up to set email alerts
|

CiXTH29 and CiLEA4 Role in Water Stress Tolerance in Cichorium intybus Varieties

Abstract: Drought causes massive crop quality and yield losses. Limiting the adverse effects of water deficits on crop yield is an urgent goal for a more sustainable agriculture. With this aim, six chicory varieties were subjected to drought conditions during seed germination and at the six week-old plant growth stage, in order to identify some morphological and/or molecular markers of drought resistance. Selvatica, Zuccherina di Trieste and Galatina varieties, with a high vegetative development, showed a major germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…To resume growth and adapt to water stress, plant cells must regain their ability to loosen the cell wall and incorporate new polymers over an extended period of time; this helps to avoid cell-wall disruption [ 26 , 27 ]. For example, increased xyloglucan content in the cell walls of bundle xylem vessels is a potential feature of resistance to drought stress in some chicory varieties [ 28 ]. Expression of xyloglucan endo-transglycosylase/hydrolases (XTHs) genes AtXTH4, AtXTH9 and CiXTH29 promoted cell-wall remodeling and contributed to better plant tolerances to drought stress [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To resume growth and adapt to water stress, plant cells must regain their ability to loosen the cell wall and incorporate new polymers over an extended period of time; this helps to avoid cell-wall disruption [ 26 , 27 ]. For example, increased xyloglucan content in the cell walls of bundle xylem vessels is a potential feature of resistance to drought stress in some chicory varieties [ 28 ]. Expression of xyloglucan endo-transglycosylase/hydrolases (XTHs) genes AtXTH4, AtXTH9 and CiXTH29 promoted cell-wall remodeling and contributed to better plant tolerances to drought stress [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased xyloglucan content in the cell walls of bundle xylem vessels is a potential feature of resistance to drought stress in some chicory varieties [ 28 ]. Expression of xyloglucan endo-transglycosylase/hydrolases (XTHs) genes AtXTH4, AtXTH9 and CiXTH29 promoted cell-wall remodeling and contributed to better plant tolerances to drought stress [ 26 , 27 , 28 , 29 ]. In this study, transcriptome sequencing analyses revealed that a large number of genes related to the synthesis/degradation of cell-wall constituents as well as genes regulating wax synthesis were specifically enriched in both oat varieties with different drought resistances, indicating that the up- or downregulation of those genes is closely related to an increase in cell-wall composition and wax crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Maize was also intolerant of waterlogging stress, and the trefoil stage was the most sensitive period for it [118,119]. Water stress has a different impact on crops mainly based on the stage of plant development; such stress is especially critical during reproductive development, and seed germination is drastically affected by water availability [120,121]. Furthermore, drought experienced during flowering has been reported to lead to infertility in wheat [122].…”
Section: Water Stress On Food Productionsmentioning
confidence: 99%
“…Principally, the identification of stress-related genes provides a strong tool for improving water stress tolerance. Indeed, a large number of stress-response genes are activated through complex signal transduction networks, promoting the synthesis of many functional proteins related to the capability to resist water stress in the tolerance mechanisms [120,[155][156][157][158][159]. Several genes have been identified to increase drought tolerance in plants: high basal levels of the CiLEA4 and CiXTH29 genes in chicory seem to enhance drought tolerance [120]; a transcription factor involved in the pathway of LEA and dehydrin gene expression, TaNAC69, has the same effect in wheat [159]; and the heat shock protein HSP70-1 activates the drought stress tolerance mechanisms in tobacco [160].…”
Section: Adaptation Strategies To Integrate Resilience Food Security ...mentioning
confidence: 99%
See 1 more Smart Citation